The line of beauty [videorecording (DVD)] - Dibb, Saul; Stevens, Dan, 1982-; Atwell, Hayley, 1982-; McInnerny, Tim; Krige, Alice, 1954-; Hollinghurst, Alan (BBC Video ; Distributed by Warner Home Video, 2006)
This three-part saga is set during the Thatcherite 1980s. A story of love, class, sex, and money, as seen through the eyes and experiences of a young gay man, from the euphoria of falling in love to the tragedy of AIDS.